Commercial carbon nanotube as rear contacts for industrial p-type silicon solar cells with an efficiency exceeding 23%. (15th January 2023) - Gao, Qing; Yan, Jun; Li, Han; Chen, Jingwei; Yang, Xueliang; Bai, Yuhua; Zhang, Xuning; Chen, Bingbing; Guo, Jianxin; Duan, Weiyuan; Han, Kaixin; Li, Feng; et al.
Abstract: Commercially available single wall carbon nanotube (SWCNT) soots are combined with an organic passivation scheme and shown to be an efficient rear contact and alternative to ALD-Al2 O3 /PECVD-SiNx/laser treatment in conventional passivated emitter and rear cell (PERC) solar cells. Both low carbonaceous purity 60–70% and 95% SWCNTs are tested and a power conversion efficiency of over 23% is demonstrated. The approach is simple, scalable and completely eliminates the metal-semiconductor contact known to cause high interfacial recombination in PERC technology. A low reverse saturation current density ( J 0 ) is achieved by varying the concentration and species of SWCNTs used and a full-area back surface field on an industrial sized (275.54 cm 2 ) solar cell is obtained. Graphical abstract: This work proposes a commercially available SWCNT soot mixed with Nafion to replace the traditional back structure of PERC solar cells to form a new carbon nanotube-organic passivating contacted p-type silicon solar cells. This results in a dramatically simplified production process. A full-area back surface field and a record efficiency of 23.03% is achieved. Image 1